2021
DOI: 10.3390/ma14061328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Hydration Characteristics and Anti-Washout Resistance of Non-Dispersible Underwater Concrete with Nano-SiO2 and MgO

Abstract: In this paper, the effect of nano-SiO2 (NS) and MgO on the hydration characteristics and anti-washout resistance of non-dispersible underwater concrete (UWC) was evaluated. A slump flow test, a viscosity test, and setting time measurement were conducted to identify the impacts of NS and MgO on the rheological properties of UWC. The pH and turbidity were measured to investigate the anti-washout performance of UWC mixes. To analyze the hydration characteristics and mechanical properties, hydration heat analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…However, the degree of purity rapidly changed afterward for MI, MII, and MIII in the first group. These results are considered excellent compared with other studies that have investigated the addition of nano SiO2 and nano MgO to underwater concrete, in which the pH values ranged between 11.1 and 11.9 [2].…”
Section: Ph Factor and Turbidity Tests Of Ndrpcsupporting
confidence: 68%
See 2 more Smart Citations
“…However, the degree of purity rapidly changed afterward for MI, MII, and MIII in the first group. These results are considered excellent compared with other studies that have investigated the addition of nano SiO2 and nano MgO to underwater concrete, in which the pH values ranged between 11.1 and 11.9 [2].…”
Section: Ph Factor and Turbidity Tests Of Ndrpcsupporting
confidence: 68%
“…Otherwise, previous studies [2,[28][29][30] have used this test to predict the washout resistance of underwater concrete. Samples of NDRPC incorporating 15% SF showed that 58 to 258 NTU at 1 minute became 85 to 569 NTU at 15 minutes.…”
Section: Ph Factor and Turbidity Tests Of Ndrpcmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that SiO 2 and MgO decreased slump, primary and secondary setting time, increased viscosity and improved resistance against scouring. Compressive strength increased with SiO 2 , while MgO showed a slight decrease in strength [11].…”
Section: State-of-the-art Reviewmentioning
confidence: 93%
“…Researchers Liu et al [20] found that adding mineral powder improved the pore size distribution and reduced the porosity of UWC, which improved the impermeability of concrete at a macrolevel. Jeon et al [21] investigated the effect of nano-SiO 2 (NS) and MgO on the hydration characteristics and antiwashout resistance of UWC. In this study, they demonstrated that NS and MgO reduced slump flow, increased viscosity, and enhanced the antiwashout resistance of UWC.…”
Section: Introductionmentioning
confidence: 99%